Proposed areas of cooperation among ASEAN countries in the fields related to satellite remote sensing (SRS), geographic information system (GIS) & environment (Pakistan Space and Upper Atmospheric Research Commission, 2006)
Presentation to the 14 Meeting of the ASEAN Sub-Committee on Space Technology and Applications (SCOSA), 23 August 2006
pdf format (27 slides)
Keywords: Satellite remote sensing; Satellite technology